A Systematic Literature Review of the Use of Pop-Up Books in Mathematics Education: Trends, Methods, and Learning Outcomes - Ankai Wahyuni Tanjung Handayani; Mardiyana; Laila Fitriana; Farida Nurhasanah (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2026)
Mathematics learning requires instructional media that can help students understand abstract concept in a more meaningful and engaging way. One medium that has attracted increasing attention is pop-up book. Although numerous studies have investigated the use of pop-up books in mathematics education, the finding remain scattered across different educational levels, mathematical topics, and research approaches.  Therefore, a comprehensive synthesis is needed to prove a clearer understanding of research trends and finding in this area.  This study aims to analyze the implementation of pop-up book in mathematics learning through a Systematic Literature Review (SLR) approach. The review was conducted using the PRISMA framework. Data were collected from Scopus, Semantic Scholar, and Google Scholar, with publication period between 2016 and 2025.  After the screening process, 23 articles met the established criteria.  The findings indicate that pop-up book are most frequently applied in geometry topics, especially at the elementary and junior high school levels.   Research and Development (R & D) was the most commonly used approach with pop-up book primarily serving as instructional media. Overall, the reviewed studies reported positive effects on students’ learning motivation, conceptual understanding, and problem-solving skills, mathematics communication, and learning achievement.  In conclusion, pop-up book have considerable potential to support mathematics learning across various topics and educational levels.  However, existing studies mainly focus on teacher developed media, while students ‘involvement in designing and creating pop-up book remain largely unexplored. Future research should investigate student-centered approaches that integrate pop-up book creation into mathematics learning.